Systematic Literature Review: “Service Innovation And Customer Experience” - M. Dayat; Sudarmiatin Sudarmiatin; Budi Eko Soetjipto; Cipto Wardoyo (Pusat Riset dan Inovasi Nasional, 2023)
In today's competitive business environment, customer experience has become an increasingly important factor in determining the success of a business. As a result, businesses are constantly looking for ways to improve the experience of their customers through service innovation. Service innovation refers to the development and implementation of new or improved services that better meet the needs and wants of customers. The objective of service innovation is to provide a unique and differentiated customer experience that sets a business apart from its competitors. Although the importance of service innovation in improving customer experience is widely recognized, there is a lack of clarity on how service innovation can be effectively implemented to enhance customer experience. This systematic literature review (SLR) aims to fill this gap by synthesizing existing research on service innovation and its impact on customer experience.